Automobile engineering: automobile engines including electrical equipments - Singh, Kirpal (Standard Publishers Distributors, 1996)
Automobile engineering: automobile engines including electrical equipments / Singh, Kirpal. -- New Delhi: Standard Publishers Distributors, 1996 629.8092 Si617 V2 7th ed No. of Copies : 1